Comparison of microbial colonization rates between central venous catheters and peripherally inserted central catheters - Vassiliki Pitiriga; John Bakalis; Kalliopi Theodoridou; Evangelia Dimitroulia; George Saroglou; Athanasios Tsakris (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background Central venous catheters (CVCs) and peripherally inserted central catheters (PICCs), have been widely used as intravascular devices in critically ill patients. However, they might evoke complications, such as catheter colonization that has been considered as predisposing factor for central line-associated bloodstream infections (CLABSIs). Although numerous studies have compared the risk of bloodstream infections between PICCs and CVCs, comparative studies on their colonization rates are limited. Objectives The episodes of catheter colonization in critically ill patients with CVCs or PICCs were retrospectively analysed during a two-year period in a Greek tertiary care hospital and colonization rates, microbial profiles and antimicrobial susceptibility patterns were compared. Methods Clinical and laboratory data of consecutive hospitalized critically-ill patients who underwent PICC and CVC placement between May 2017–May 2019 were analysed. All catheters were examined by the semiquantitative culture technique for bacterial pathogens, either as a routine process after catheter removal or after suspicion of infection. Species identification and antimicrobial resistance patterns were determined by the Vitek2 automated system. Results During the survey period a total of 122/1187 (10.28%) catheter colonization cases were identified among CVCs and 19/639 (2.97%) cases among PICCs (p = 0.001). The colonization rate was 12.48/1000 catheter-days for the CVC group and 1.71/1000 catheter-days for the PICC group (p < 0.001). The colonization rate per 1000 catheter-days due to multidrug-resistant organisms (MDROs) was 3.85 in all study cases, 7.26 (71/122) in the CVC group and 0.63 (7/19) in the PICC group (p < 0.001). Within the CVC group, the most common microorganism isolated was MDR Acinetobacter baumannii (n = 38, 31.1%) followed by MDR Klebsiella pneumoniae (n = 20, 16.4%). In the PICC group, the predominant microorganism isolated was Candida spp. (n = 5, 23.8%) followed by MDR K. pneumoniae and MDR A. baumannii in equal numbers (n = 3, 14.2%). Conclusion PICC lines were associated with significantly lower colonization rates comparing to the CVC ones. In addition, patterns of microbial colonization revealed a trend over the predominance of MDR gram-negatives in CVCs suggesting that PICCs might be a safer alternative for prolonged inpatient intravascular access. Prevention programs directed by local microbial ecology may diminish catheter colonization rates and CLABSIs.